RESPON TANAMAN SAWI PAKCOY (Brassica rapa) TERHADAP LARUTAN HARA (KOTORAN IKAN) PADA SISTEM AKUAPONIK - Astuti, Sri; Larasati, Wenda Ayu (Universitas Bengkulu, 2019)
Aquaponics is a combined cultivation method between fisheries and plants in one container. Aquaponics constantly use water from fish to plant management and on contrary from plants to fish ponds. In aquaponics, animal excretion is given to plants to be broken down into nitrates and nitrites through natural processes, and utilized by plants as nutrients. The aim of this research was to determine the response of Pakcoy green cabbage (Brassica rapa) to the nutrient solution nutrient (fish droppings) in the aquaponic system. This research was conducted on December 20, 2017 to February 20, 2018. The yield data from green cabbage plants (Brassica rapa) that had been obtained was analyzed using descriptive analysis. Based on the results of the study, by providing nutrient solutions in the form of fish droppings on green cabbage plants grown using the aquaponic system responds to the symptoms of yellow leaves and the size of small tubers.